2018
DOI: 10.1002/jbio.201800066
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optical imaging of the viable epidermis around the nailfold capillaries for the assessment of heart failure severity in humans

Abstract: Heart failure (HF) is among the socially significant diseases, involving over 2% of the adult population in the developed countries. Diagnostics of the HF severity remains complicated due to the absence of specific symptoms and objective criteria. Here, we present an indicator of the HF severity based on the imaging of tissue parameters around the nailfold capillaries. High resolution nailfold video capillaroscopy was performed to determine the perivascular zone (PZ) size around nailfold capillaries, and 2-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Autofluorescence (AF), i.e., intrinsic fluorescence of endogenous fluorophores, is extensively used in a range of biomedical applications [1]. Being non-invasive and label-free method, it has proven to be an indispensable tool for intraoperative diagnostics (fluorescence-guided surgery) [2], analysis of biofluids (blood [3,4], saliva [5], urine [6,7]), optical biopsy [8][9][10] etc. AF analysis is usually performed on a phenomenological basis, which means discrimination between objects (e.g., normal and pathological tissues, or between different components of the tissue) basing on differences in their AF intensity, spectral band shape or lifetime [11,12] and photobleaching rate [13].…”
Section: Introductionmentioning
confidence: 99%
“…Autofluorescence (AF), i.e., intrinsic fluorescence of endogenous fluorophores, is extensively used in a range of biomedical applications [1]. Being non-invasive and label-free method, it has proven to be an indispensable tool for intraoperative diagnostics (fluorescence-guided surgery) [2], analysis of biofluids (blood [3,4], saliva [5], urine [6,7]), optical biopsy [8][9][10] etc. AF analysis is usually performed on a phenomenological basis, which means discrimination between objects (e.g., normal and pathological tissues, or between different components of the tissue) basing on differences in their AF intensity, spectral band shape or lifetime [11,12] and photobleaching rate [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence decay parameters of the endogenous fluorophores, such as NAD(P)H and FAD, allow evaluations of the metabolic status of cells and tissues 17 , the simultaneous use of cells’ morphology and their fluorescence decay parameters allows one to distinguish between different types of cells both in vitro and in vivo using FLIM 39 , 40 . The use of the multiphoton excitation in the near-infrared range permits to scan relatively deep tissue layers, hence to localize and characterize structural proteins, to determine the parameters of the microcapillaries and study physiological processes in vivo 27 , 41 . FLIM has also been used in the assessment of the properties of the engineered biomaterials 18 – 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the CHF progress is normally accompanied by some metabolic abnormalities that are particularly evident in the human skin content change. For example, Shirshin et al [16] reported on water and electrolyte content change in the viable skin epidermis that is controlled by interstitial fluid retention when diagnosing CHF. Other biomarkers in skin, including lipid and collagen parameters [4] have been put forward as potential chemical CHF‐related changes that also have a direct impact on the skin component concentrations.…”
Section: Introductionmentioning
confidence: 99%